Non-Invasive Neuromodulation for Drug-Resistant Epilepsy in Children: A Randomized Controlled Trial of Transcranial Magnetic Stimulation (TMS) versus Vagus Nerve Stimulation (VNS) in Jakarta, Indonesia - Febria Suryani; Rinna Azrida; Linda Purnama; Vania Delma; Desiree Montesinos (Scientific Journal of Pediatrics, 2025)
Introduction: Drug-resistant epilepsy (DRE) significantly impacts the quality of life in children. While vagus nerve stimulation (VNS) is an established treatment, repetitive transcranial magnetic stimulation (rTMS) offers a non-invasive alternative. This study aimed to compare the efficacy and safety of rTMS versus VNS in a pediatric DRE population in Jakarta, Indonesia. Methods: This was a single-center, randomized, controlled, open-label trial conducted at Private Hospital, Jakarta. Children aged 5-18 years with DRE, defined as failure to achieve seizure freedom despite adequate trials of two appropriate antiepileptic drugs (AEDs), were randomly assigned (1:1) to receive either rTMS or VNS. The primary outcome was the percentage reduction in seizure frequency at 6 months post-intervention compared to baseline. Secondary outcomes included responder rate (≥50% seizure reduction), quality of life (QoL) using the PedsQL, cognitive function (using standardized neuropsychological tests), and adverse events. Results: A total of 60 children were randomized (30 rTMS, 30 VNS). At 6 months, the mean percentage reduction in seizure frequency was significantly greater in the rTMS group (48.5%, SD 15.2%) compared to the VNS group (35.2%, SD 12.8%) (p = 0.001). Responder rates were 63.3% for rTMS and 46.7% for VNS (p = 0.17). PedsQL scores showed a significant improvement in the rTMS group compared to baseline in the psychosocial health summary score (p = 0.005), but not the VNS group (p=0.1). No significant differences were observed in cognitive function between the groups. Adverse events were generally mild and transient in both groups, though VNS was associated with more voice alteration and coughing. Conclusion: rTMS demonstrated superior efficacy in reducing seizure frequency compared to VNS in this Indonesian pediatric DRE population. While VNS is an established method, rTMS may present a non-invasive and potentially more effective therapeutic alternative. Further, larger, multicenter studies are warranted to confirm these findings and explore long-term outcomes.